Habitat restoration benefits wild bees: A meta‐analysis. Issue 2 (22nd October 2017) - Tonietto, Rebecca K.; Larkin, Daniel J.
Abstract: Pollinator conservation is of increasing interest in the light of managed honeybee ( Apis mellifera ) declines, and declines in some species of wild bees. Much work has gone into understanding the effects of habitat enhancements in agricultural systems on wild bee abundance, richness and pollination services. However, the effects of ecological restoration targeting "natural" ecological endpoints (e.g. restoring former agricultural fields to historic vegetation types or improving degraded natural lands) on wild bees have received relatively little attention, despite their potential importance for countering habitat loss. We conducted a meta‐analysis to evaluate the effects of ecological restoration on wild bee abundance and richness, focusing on unmanaged bee communities in lands restored and managed to increase habitat availability and quality. Specifically, we assessed bee abundance and/or richness across studies comparing restored vs. unrestored treatments and studies investigating effects of specific habitat restoration techniques, such as burning, grazing, invasive plant removal and seeding. We analysed 28 studies that met our selection criteria: these represented 11 habitat types and 7 restoration techniques. Nearly all restorations associated with these studies were performed without explicit consideration of habitat needs for bees or other pollinators. The majority of restorations targeted plant community goals, which could potentially have ancillary benefits for bees. Restoration had overall positive effects on wild bee abundance and richness across multiple habitat types. Specific restoration actions, tested independently, also tended to have positive effects on wild bee richness and abundance. Synthesis and applications . We found strong evidence that ecological restoration advances wild bee conservation. This is important given that habitat loss is recognized as a leading factor in pollinator decline. Pollinator responses to land management are rarely evaluated in non‐agricultural settings and so support for wild bees may be an underappreciated benefit of botanically focused management. Future restoration projects that explicitly consider the needs of wild bees could be more effective at providing nesting, foraging and other habitat resources. We encourage land managers to design and evaluate restoration projects with the habitat needs of wild bee species in mind. Abstract : We found strong evidence that ecological restoration advances wild bee conservation. This is important given that habitat loss is recognized as a leading factor in pollinator decline. Pollinator responses to land management are rarely evaluated in non‐agricultural settings and so support for wild bees may be an underappreciated benefit of botanically focused management. Future restoration projects that explicitly consider the needs of wild bees could be more effective at providing nesting, foraging and other habitat resources. We encourage land managers to design and evaluate restoration projects with the habitat needs of wild bee species in mind.